2011
DOI: 10.1016/j.jtcvs.2011.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Expanded polytetrafluoroethylene conduits and patches with bulging sinuses and fan-shaped valves in right ventricular outflow tract reconstruction: Multicenter study in Japan

Abstract: Fan-shaped ePTFE valved conduits and patches with bulging sinuses have a high freedom from reoperation and prevent pulmonary insufficiency. They represent a promising material for RVOT reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 20 publications
2
69
0
2
Order By: Relevance
“…Miyazaki and colleagues [20] reported an excellent mid-term outcome of a handmade valved ePTFE conduit with bulging sinuses, in the multicenter study in Japan, with no conduit reoperation in large conduits for 10 years and good conduit valve function [20]. The bulging sinuses represented the shape of sinus of Valsalva and were expected to enhance handmade valve function [15].…”
Section: Commentmentioning
confidence: 99%
“…Miyazaki and colleagues [20] reported an excellent mid-term outcome of a handmade valved ePTFE conduit with bulging sinuses, in the multicenter study in Japan, with no conduit reoperation in large conduits for 10 years and good conduit valve function [20]. The bulging sinuses represented the shape of sinus of Valsalva and were expected to enhance handmade valve function [15].…”
Section: Commentmentioning
confidence: 99%
“…8 Miyazaki et al reported the usefulness of fan-shaped ePTFE valve conduits with bulging sinuses during mid-term follow-up. 17 ePTFE valves should be covered by a thin fibrous tissue and show focal regions of endothelialization. The ePTFE valve cannot be expected to develop adaptive growth during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of using ePTFE is that it provides a better modulus match than most continuous polymers for many soft biological tissue application [9], easier availability, higher biocompatible and resistance to degeneration or calcification [4]. Recently, ePTFE valved conduits with bulging sinuses of Valsava for RVOT reconstruction has been reported and showed excellent early to mid-term results in patients [10].…”
Section: Introductionmentioning
confidence: 99%